Antimicrobial Resistance, Biofilm Formation and mecA Characterization of Methicillin-Susceptible S. aureus and Non-S. aureus of Beef Meat Origin in Egypt - Osman, Kamelia M.; Amer, Aziza M.; Badr, Jihan M.; Helmy, Nashwa M.; Elhelw, Rehab A.; Orabi, Ahmed; Bakry, Magdy; Saad, Aalaa S. A. (Frontiers in Microbiology, 2016)
Methicillin-resistant Staphylococcus aureus (MRSA) have been found in various farm animal species throughout the world. Yet, methicillin-susceptible S. aureus (MSSA), methicillin-susceptible non-S. aureus (MS-NSA) and methicillin-resistant non-S. aureus (MR-NSA) were not investigated. Therefore, we persued to determine the diversity in their phenotypic virulence assay, phenotypic antimicrobial resistance profile and molecular characterisation in one of the food chains in Egypt. Samples were collected during 2013 from beef meat at retail. Twenty seven isolates comprising five species (S. hyicus, S. aureus, S. schleiferi subsp. coagulans, S. intermedius and S. lentus) were characterized for their antibiotic resistance phenotypic profile and antibiotic resistance genes (mecA, cfr, gyrA, gyrB and grlA). Out of the 27 Staphylococcus isolates only one isolate was resistant to the 12 antibiotics representing nine classes. Raw beef meat sold across the Great Cairo zone, contains 66.7% of MRS, with highest prevalence was reported in S. aureus (66.7%), while the MRS non-S. aureus strains constituted 66.7% from which S. hyicus (60%), S. intermedius (33.3%), S. schleiferi subsp. coagulans (100%) and S. lentus (100%) were MRS. Seven S. aureus, six S. hyicus, four S. schleiferi subsp. coagulans, three S. intermedius and one S. lentus isolates although being resistant to oxacillin yet, 11/27 (40.7%) carried the mecA gene. At the same time, the cfr gene was present in 2 of the nine S. aureus isolates, and totally undetectable in S. hyicus, S. schleiferi subsp. coagulans, S. intermedius and S. lentus. Although global researches largely focused into MRSA and MR-NSA in animals on pigs, the analysis of our results stipulates that buffaloes and cattle could be MRSA dispersers and that this theme is not specific to pigs. Detection of MSSA virulence determinants is a must, as although oxacillin resistance may be absent yet, the MSSA may carry the virulence determinants which could be a source of perilous S. aureus for the human community.